Produção do gênero Carta de solicitação no 9° ano do ensino fundamental: a escrita como prática social. - Amorim, Andreza Soares Espínola de (2016)
For several decades, Portuguese Language teaching in schools was founded on a normative perspective, turning almost exclusively to the assimilation of grammar rules or standard language. In this context, the activities of reading and writing took place in a decontextualized way, unrelated to students experience, which made difficult the development of these skills. Against this teaching model, the work proposal from discourse genres, in which fits the current study, seeks to explore text in real conditions of use, highlighting the communicative function beyond the formal aspects of each genre. Based on theorists as Bakhtin (2011) and Marcuschi (2010) with regard to the conception of discoursive/ textual genre, and Dolz, Schneuwly and Noverraz (2011) in relation to Didactic Sequences, among others. The present study aims to prepare 9th grade students of public Elementary School located in the countryside of Pedro Régis (PB) to recognize and produce the genre letter of request from its linguistic and discursive functioning and its social use, investigating the development of skills and argumentative strategies, from the proposed contextualized textual genre production and subsidized by a didactic sequence. The genre was chosen for enabling writing with a concrete social function: request rights and persuade a specific interlocutor, through argument, to take action on any situation. Counting with ten (10) volunteer students, the corpus of our analysis was made for the first and last version of the texts produced by them during the Sequence's implementation. Based on the first productions, we mapped the main difficulties presented by students about genre, from that mapping, modules / workshops were developed aiming to overcome these difficulties. After the comparative analysis between the two versions of the letters, we identified that advances were more significant in the following ways: informativeness, cohesion mechanisms and development of argument. Therefore, the results indicate that the use of DS in the teaching-learning process of investigated genre contributed to enlarge the linguistic-discursive competence of students.